Colour, Culture and Deixis as Elements of Meaning in the Discourse of Advertising Mobile Telecommunications Networks in Nigeria - Adegoju, Adeyemi (Public Journal of Semiotics, 2008)
This article examines the appropriation of sign systems in the discourse of marketing the services of mobile telecommunications networks in Nigeria. The paper attempts to interpret the sign systems deployed in these marketing strategies in relation to the contextual background within which they operate, revealing multiplicities of meaning that are tied to the service providers’ ideological perceptions, which to a large extent appeal to the audience’s sentiments and in some cases abuse their sensibilities.